Investigating the impact of a non integrated accounting information system on organisational performance: a case study of Zimpapers (Manica Post) - Mangwende, Kudakwashe (Midlands State University, 2015)
The aim of the research is to investigate the impact of using non-integrated accounting information systems on organizational performance. The literature on the research study constituted all the objectives of the research study and what other authors have said about the development of integration from traditional accounting systems. Questionnaires were used as the main data collection instruments essential in the collection of data. Primary and Secondary sources were both used to obtain data. The information obtained from the data collected was analyzed by making use of a spread sheet and it was presented by making use of simple tables and graphs. From the research conducted the research findings indicate that there is a correlation between an accounting information system and organizational performance. The use of non-integrated accounting information system has a significant negative bearing on organizational performance as this was the main research objective of the study. The research findings also show that the competence of personnel and input controls are some of the attributes that affects data quality within an organization. The research study ultimately reflects that the implementation of Enterprise Application Integration (EAI) system was arguably chosen as the best practice of integration, through application integration and external business integration.